Fly Ash as Stimulant for Anaerobic Digestion: Effect over Hydrolytic Stage and Methane Generation Rate - Huilinir-Curio, C; Montalvo-Martinez, S (IWA Publishing, 2019)
Thermoelectric fly ash was used as a micronutrient source for microorganisms in the anaerobic digestion process of thermally pretreated secondary sludge. The obtained results suggested that fly ash improved CH4 generation in the conversion of volatile fatty acids into CH4 and the fly ash contributed in the particulate organic solubilization. The maximum CH4 production rate increased from 6.52 mL/L/d to 22.59 mL/L/d when fly ash was added at a dosage of 150 mg/L in biochemical methane potential tests compared with tests with no added ash. Also, the kinetic constants of the hydrolysis of particulate organic matter were obtained in both cases (with and without added ash) in batch reactors using a first-order kinetic model. In the case of no addition, the first-order kinetic parameter was 0.019±0.002/day while with ashes this value increased to 0.045±0.000/day. Therefore, the addition of fly ash improved CH4 generation and hydrolytic kinetics in different orders of magnitude.